The GPR30 agonist G-1 promotes hair growth via Wnt/Hedgehog signaling in mice - Yamano, Mayu; Yamanaka, Yuto; Nishikawa, Shota; Masujima, Yuki; Ohue-Kitano, Ryuji; Kimura, Ikuo (Frontiers in Pharmacology, 2025)
BackgroundGPR30 is a membrane-associated receptor involved in rapid, non-genomic estrogen signaling. Estrogen significantly influences hair growth and susceptibility to hair loss, with differences primarily driven by hormonal factors. While estrogen’s role in regulating hair follicle cycling is recognized, its precise molecular mechanisms remain unclear. This study investigates the role of GPR30 in hair follicle biology and evaluates its potential as a therapeutic target for estrogen-mediated hair loss disorders.MethodsThe GPR30 selective agonist G-1 was administrated to female Gpr30-deficient mice with a C57BL/6J background and human hair follicle dermal papilla cell, and the effects on hair growth and the molecular signaling were evaluated.ResultsWe demonstrate that GPR30 is abundantly expressed in mouse skin, particularly during the anagen phase of the hair follicle cycle, implicating it in hair growth regulation. Activation of GPR30 using the selective agonist G-1 in mouse skin and human dermal papilla cells significantly upregulated Wnt/Hedgehog signaling, which are key pathways promoting hair growth. These effects were absent in Gpr30-deficient mice or in those administered a GPR30 antagonist, confirming the essential role of GPR30 in estrogen-mediated regulation of hair follicle activity.ConclusionOur findings underscore the importance of GPR30 in modulating hair growth and suggest that GPR30, along with its selective agonists, holds promise as a novel therapeutic target for treating hair loss disorders and other estrogen-responsive conditions.